The evolution of physical attributes in elite ski racers aged 17 to 20 during the olympic training period - Golovachev A.I.; Kolykhmatov V.I.; Grushin A.A.; Shirokova S.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to investigation of the development of physical attributes in elite ski racers aged 17 to 20 during the Olympic training period. Методы и организация исследования. The research involved 11 athletes from the junior Russian national ski team, aged between 17 and 20, with a training experience ranging from 5 to 8 years. These athletes, with qualifications ranging from CMS to MS, participated in a series of comprehensive tests as part of the NMO program, which was conducted at the ROC Innovation Center and the Federal State Budgetary Institution FNC VNIIFK. The tests were conducted at the beginning and end of the preparatory period for the 2022-23 and 2023-24 sports seasons. The examination protocol included assessments of the athletes’ explosive strength in the upper and lower body, as well as their speed and strength endurance in the upper body. The study employed a variety of research methods, including ergometry with test protocols on a strain gauge platform (performing jumping exercises at maximum power) and a SkiErg ergometer, Concept-2 (USA), which replicates the movement patterns of simultaneous strokes. Additionally, heart rate monitoring and methods of mathematical statistics were employed. The implementation of test protocols, instruments, and methods for monitoring the studied parameters was based on methodological guidelines developed for assessing the development of the key physical attributes of athletes in the national teams of Russia and their immediate reserves. Results and conclusions. The findings of the comparative examination of the analyzed parameters suggest that a distinctive characteristic of the development of the key physical attributes among ski racers at the conclusion of the preparatory phase of their second year of training is a multilevel rise in the absolute and relative values of the explosive strength of the upper and lower limbs (work in one movement: Aabs. +2,3% and Altn. +1,8%), the legs (strength gradient: Chabs. +3,5% and Jotn. +3,0%), and the hands (power in the 5 PMR test: Nabs. +4,3% and Retn. +3,9%). Simultaneously, the disparities in relation to the model level of the 2022 Olympian are being eliminated, with a pronounced manifestation in the level of explosive arm strength (-7,3% and -7,1%), approaching the lower limit of the model level. However, there remains a significant lag in the level of explosive leg strength (-13,4% and -9,6%) and speed and strength endurance of the arms (-13,5% and -9,5%), particularly in absolute terms, which reflects their dependence on the overall size of the body.